Effect of indigenous herbal preparations on coccidiosis of poultry (Research in Agriculture Livestock and Fisheries, 2016)
Coccidiosis is a protozoan disease in chickens caused by Eimeria spp with great economic significance. The disease can be controlled by using modern anticoccidial drugs. However large scale and long term use of anticoccidial drugs has led to the resistance. Phytotherapy can be used successfully as an alternative coccidiosis control strategy. Ninety six chicks experimentally infected with coccidiosis were used in the present study. The chicks were divided into 24 groups and were treated with the crude watery extract (10%) of mango, pineapple, guava, chutra leaves and thankuni at the dose rate of 1ml, 5ml and 10ml per Kg body weight as well as one group was treated with Embazine® at recommended dose. The effects of these drugs were evaluated by oocyst count from faecal sample and the mortality rate. The result shows that the 10ml/Kg dose worked better than other dose. In this dose oocyst count significantly decreased (P< 0.01) at the day of 4 (mango), 2 (pineapple), 12 (guava), 2 (chutra) and 4 (thankuni). No oocyst found in feces at the day 8 (chutra and thankuni), 12 (mango and pineapple) whereas on day 12 it shows oocyst in feces in case guava. It shows that mortality encounter 75% in mango and guava group, 50% in pineapple and thankuni group, wheras no mortality recorded in chutra group. After completion of experiment it was noted that chutra leaves was most effective at the dose rate of 10 ml/kg body weight and effective near about Embazine.Res. Agric., Livest. Fish.3(1): 145-149, April 2016